Działalność szkoły polskiej w Algierze w czasie II wojny światowej w świetle archiwaliów oraz wspomnień - Śliwak, Katarzyna (Acta Universitatis Lodziensis. Folia Historica, 2015)
In the paper the author presented a historical overview of the history of Polish emigration in Algeria until the outbreak of World War II. The rest of the work described the circumstances of the assumptions Polish secondary school in Algiers, the activities of local teachers, the support provided by the Polish government in exile in London. The last part of the work is based on memories former schoolgirl Romana Łukasik to show her experience in school life, conditions of life, emigration in Algeria.